The Influence of Zeitgeist on Historical Content in High School History Textbooks Curriculum 1975-2004 - Marlina, Marlina (Universitas Negeri Semarang, 2019)
This study explores the relationship between the ruling regime and the hegemonic educational framework by examining the content of history textbooks within this context. The research used historical methods to collect comprehensive data from official and unofficial written historical sources. The findings indicate that the prevailing spirit of the age, as dictated by the authorities in power, significantly influenced the content of history education. Specifically, the study reveals that the educational agenda was strategically utilized to sustain and reinforce Suharto's power through the history curriculum from 1975 to the KBK Curriculum in 2004. The results demonstrate how the regime's interests permeated the educational sphere, shaping the historical narratives presented to students in a way that served to legitimize and perpetuate the ruling authority. This manipulation of historical content within textbooks underscores the broader dynamics of power and control in the educational sector, illustrating the extent to which education can be co-opted to maintain political dominance. Through this detailed analysis, the study contributes to a deeper understanding of the intersection between political authority and educational content, highlighting education's critical role in preserving hegemonic power.